Johnson's World : on Mercator's projection. - Johnson, A. J. (Alvin Jewett), 1827-1884 (A.J. Johnson, 1865)
Map shows seven continents, Oceanica, and Australasia with major cities and political divisions; "Alaska" [not Russian America], "Hindostan" [India], Russia and Russian Empire, Chinese Empire. Includes explorer's routes with dates. Relief shown by hachures. Scale not given.